Design of Robust Centralized PID Optimized LQR Controller for Temperature Control in Single-Stage Refrigeration System - Ekengwu, Bonaventure Onyeka; Eze, Paulinus Chinaenye; Muoghalu, Chidiebere Nnaedozie; Asiegbu, Christopher Nnaemeka; Achebe, Patience Nkiruka (IAES Indonesian Section, 2024)
Refrigeration systems are used for many purposes such as food preservation, cooling and others. They require controller to ensure that the refrigerating cycle can go ON and OFF to maintain a setpoint temperature. For instance, in preservation of food or other perishables, deterioration can occur without efficient system to ensure that temperature within refrigerating space is kept at a setpoint value. This paper presents robust centralized proportional integral and derivative (PID) optimized linear quadratic regulator (LQR) temperature control system for single-stage refrigeration system. A composite technique in which PID algorithm was used to adjust the gains of LQR is proposed. The model of single-stage vapour compressor refrigeration (VCR) system was established in terms of the evaporator, compressor, condenser and the expansion valve’s temperatures. An LQR was initially designed. Then a PID optimized LQR was design. The results indicated that the PID optimized LQR controller outperformed the LQR by providing 73.4% and 62.7% improvement for the evaporating temperature, 45.6% and 71.4% improvement for the compression temperature, 30% and 84.6% improvement for the condensing temperature, and lastly 72% and 70.2% improvement for the expansion temperature in terms of response time and settling time. Simulation with test data proved its robustness and effectiveness in tracking setpoint temperature. Generally, the proposed system has shown capacity to offer robust and centralized tracking in the presence of changing setpoint values.